Exploring the Therapeutic Potential of Mimosa pudica L. in Indonesian Traditional Medicine - Lusi Kristiana; Weny Lestari; Mery Budiarti Supriadi (Althea Medical Journal)
Background: Traditional medicine and traditional healers have a long history of treating diseases in Indonesia. One of the plants that has been used by traditional healers (battra) is Mimosa pudica L. (MP), which is easily found throughout Indonesia. This study aimed to explore the therapeutic potential of traditional herbal medicine containing MP by battra in Indonesia.